Moisture Conservation Practices for enhancing productivity in rainfed agriculture - Jinger, Dinesh; Sharma, Rajesh Kumar; Tomar, B S (Indian Farming, 2018)
Water is the key input for crop production in rainfed and dryland areas, therefore there is need to adopt a comprehensive approach to conserve soil moisture. Selection of suitable crops and their varieties is most important for rainfed and dryland areas. Planting of crops by altering land configuration viz. ridges and furrows, BBF, FIRB and bed planting are better for higher water productivity in both rainfed and dryland areas.